Dietary Salicornia ramosissima improves the European seabass (Dicentrarchus labrax) inflammatory response against Photobacterium damselae piscicida - Machado, Marina; Cruz, Francisco; Cunha, André; Ramos-Pinto, Lourenço; Laranjeira, Adriana; Pacheco, Mário; Rocha, Rui J. M.; Costas, Benjamín (Frontiers in Immunology, 2024)
Modern fish farming faces challenges in sourcing feed ingredients, most related with their prices, availability, and specifically for plant protein sources, competition for the limited cultivation space for vegetable crops. In that sense halophytes present the added value of being rich in valuable bioactive compounds and of being salt tolerant plants. This study assessed the inclusion of non-food fractions of S. ramosissima in European seabass diets. Different levels (2.5%, 5%, and 10%) were incorporated into seabass diets, replacing wheat meal (diets ST2.5, ST5, and ST10) or without inclusion (CTRL). Experimental diets were administered to seabass juveniles (8.62 ± 0.63 g) for 34 and 62 days, and subsequent inflammatory responses to a heat-inactivated Photobacterium damselae subsp. piscicida (Phdp) were evaluated in a time-course manner ( 4, 24, 48 and 72h after challenge). At each sampling point, seabass haematological profile, plasma immune parameters and head-kidney immune-related gene expression were evaluated. After both feeding periods, most parameters remained unaltered by S. ramosissima inclusion, nonetheless seabass fed ST10 showed an up-regulation of macrophage colony-stimulating factor 1 receptor 1 (mcsf1r1) and cluster of differentiation 8 (cd8β) compared to those fed CTRL after 62 days of feeding. Regarding the inflammatory response, seabass fed ST10 showed lower plasma lysozyme levels than their counterparts fed ST2.5 and ST5 at 24 h following injection, while at 4 h after the inflammatory stimulus seabass fed ST10 presented higher numbers of peritoneal leucocytes compared to fish fed CTRL. Moreover at 4h, ST2.5, ST5 and ST10 showed higher expression of interleukin 1β (il1β), while ST5 showed higher ornithine decarboxylase (odc), than those fed CTRL. An up-regulation of macrophage colony-stimulating factor 1 receptor 1 (mcsf1r1) and glutathione peroxidase (gpx) was also observed at 72 h in fish fed ST10 or ST5 and ST10 compared to CTRL, respectively. In conclusion, incorporating up to 10% non-food fraction S. ramosissima in feed did not compromise seabass growth or immune status after 62 days, aligning with circular economy principles. However, S. ramosissima inclusion improved the leucocyte response and up-regulated key immune-related genes in seabass challenged with an inactivated pathogen.